Integrated techno-economic and life cycle assessment of hydroformylation in microemulsion systems - Wunderlich, Johannes; Kretzschmar, Philipp; Schomäcker, Reinhard (Frontiers in Sustainability, 2024)
This paper presents the first integrated techno-economic and life cycle assessment of microemulsion systems being applied for rhodium-catalyzed hydroformylation of long-chain alkenes at industrial scale. The case study describes a projected 150 kt/a production of tridecanal (US gulf coast, 2019). The industrial success of the hydroformylation of short-chain alkenes lies in the continuous recycling of the rhodium-containing water phase. Microemulsion systems can be applied to transfer this concept to long-chain alkenes by overcoming the miscibility gap between the aqueous catalyst phase and the unipolar alkene phase and, moreover, by generating a temperature-induced multi-phase system enabling the immobilization of the catalyst and its continuous recycling, as demonstrated in miniplant operations with dodecene and rhodium/SulfoXantPhos. Customizable simulation models have been developed for scale-up and assessment of the miniplant data. Surprisingly, a profitability-driven sensitivity study indicates a base case optimum at low residence time with low alkene conversion leading to large throughput streams and high raw material purge rates. The comparison to the industrial cobalt-based benchmark system shows an economic advantage regarding net present value (Rh: 68 M$; Co: 62 M$), while about half of the environmental indicators are in favor or equivalent. In a best-case scenario considering zero leaching of expensive rhodium the net present value increases by almost 40 % accompanied by a shift to overall lower environmental impacts than the benchmark. In conclusion, the investigated miniplant data suggest microemulsion systems to be competitive when applied in continuous processes at a large scale.